PO.2.51 Hyperferritinaemia and systemic disease : SLE or still's disease?. (27th September 2022) - Kella, A; Bouziani, N; Belabbas, A; Khedim, A; Hakem, D
Abstract : Introduction: Major hyperferritinemia - after exclusion of hemochromatosis - constitutes a major biological argument of inflammation which characterizes Still's disease (SD), a condition bordering on auto-inflammatory and inflammatory disea ses. Despite the well-established diagnostic criteria for SD, its diagnosis requires the exclusion of other exclusion of other conditions such as systemic SLE and lymphomas.The clinical similiraties betwen SLE and SD are causes of diagnostic wandering. Purpose: To report case of a SLE simulating SD posing the nosological boundaries between inflammatory diseases and autoinflammatory diseases. Case Report: 16 years old woman was explored for a diffuse macular eruption with recrudescence in the evening, with deterioration in general condition, odynophagia, hectic fever, tachycardia with heartbeat at 120/min and joint damage with wrist fluxion. The evolution was enameled by a macrophage activation which responded favorably to bolus of corticosteroids. Biologically, serum ferritin level was over 1200 with low level of glycosylated ferritin. The initially negative autoimmunity assessment came back polymorphically positive including anti-Sm+ AAN. The inflammatory showed ERS at 105, polyclonal major gammaglobulinemia at 24 g/l. albuminemia at 23.97g/l, the creatinine clearance at 68.35ml/min, increase levels of ASAT at 241 (x7N), and ALAT (X4n) prothrombin at 100%, Hb level at 10.5g/dl, leucopenia at 3500 and platele rate at 97000. The medullogram showed no suspicious cells, no leishmaniasis or activated macrophages. The thyroid tests, the blood ionogram, the phosphocalcic and the hemostasis balance were without abnormalities. The triglyceride (TG) level was over 5g/l with a low HDL level of 0.30 g/l and a cholesterol level of 1.4g/l. The chest radiography revealed a small amount of pleural fluid effusion and echocardiography found a pericardial effusion with preservation of myocardial functions. The evolution was enamelled by flare-ups confining the patiente to bed, myocarditis and proteinuria leading to a renal biopsy which revealed an aspect of WHO stage 2 lupus nephropathy and signs of vasculitis. Treatment with corticosteroids, synthetic antimalarials, methotrexate allowed clinical stabilization. Discussion: The presence of evening febrile eruptions, odynophagia and hyperferritinemia associated with articular manifestations and macrophage activation argued for SD disease. The positivity of the immunological assessment and the successive occurrence during the follow-up of renal damage and myocarditis made us opt for a SLE disease in its pseudo-Still form. The background treatment remains the same for both situations. Conclusion: SLE can take on the appearance of an SD. This clinical similarity is overcome by the positivity of an autoimmunity assessment - element of exclusion of SD - which can appear secondarily.This difficult clinical situation nevertheless raises the nosological boundaries between his two conditions which fortunately benefit from a common therapy (corticosteroids, immunosuppressants such as methotrexate, biotherapy such as anti-IL 6 and anti-IL1).